Application of abdominal ultrasonography in surgical necrotizing enterocolitis: a retrospective study - Chen, Qin; Yao, Weiquan; Xu, Fengdan; Liao, Jinfeng; Li, Jinfeng; Mai, Minling; Xie, Haoqiang; He, Xiaoguang; Li, Ning (Frontiers in Microbiology, 2023)
Background Necrotizing enterocolitis (NEC) is a severe inflammatory bowel disease that may lead to perforation, causing high morbidity and mortality in preterm infants. Abdominal ultrasound (AUS) has been shown to provide benefits in diagnosing and managing NEC in recent years. Objective This study focused on the utility of AUS in the diagnosis and evaluation of surgical NEC. Patients and methods In this retrospective study, available data of the patients diagnosed from January 2019 to June 2022 were reviewed. The sensitivity and specificity of AUS in diagnosing a perforation were analyzed. Typical cases for the application of AUS in monitoring and evaluating the progression, complications, and sequela of NEC were described. Results There were 69 neonates diagnosed with NEC and examined by AUS, of whom eight patients developed a perforation. AUS was used for diagnosing a perforation in eight patients with key features of pneumoperitoneum and/or complex ascites, allowing us to find four locations of perforation, with a sensitivity and specificity of 100%. Conclusion AUS plays an important role in diagnosing and evaluating surgical NEC in newborn infants, with good sensitivity and specificity.